The Influence Of Hussein Ja'far's Preaching Through Tiktok In Motivating Adolescents In The East Kisaran Sub-District - Zulfan Sutantri Siregar; Abdullah Abdullah (UNIVERSITAS PAKUAN, 2023)
The focus of this research is to analyze the influence of Hussein Ja'far's preaching on adolescents in the East Kisaran Sub-District. The research method employed is qualitative, with data collection techniques through interviews and observations. The research is conducted in the East Kisaran Sub-District, Asahan Regency. The objective of this research is to determine the extent of the influence of the preaching content delivered by Hussein Ja'far on the level of religious activity among adolescents in the East Kisaran Sub-District. Hussein Ja'far is considered an inspirational figure for various groups, especially the youth, regardless of their religious affiliations. The findings indicate that Hussein Ja'far is a preacher who promotes values of love and tolerance, without any elements of coercion in his preaching. This approach has garnered him favor and inspiration among the youth in the East Kisaran Sub-District, Asahan Regency. Moreover, there are even non-Muslim individuals who appreciate Hussein Ja'far's preaching. His inclusive and tolerant personality allows him to connect with people from various backgrounds effortlessly.